Impact Evaluation Helps Deliver Development Projects - Legovini, Arianna; Di Maro, Vincenzo; Piza, Caio (World Bank Group, Washington, DC, 2015)
Does research add value to aid? Specifically, does impact evaluation research help or hinder the delivery of development projects? This paper analyzes the question by constructing a new data set of 100 impact evaluations and 1,135 projects approved by the World Bank between 2005 and 2011. The analysis finds that the delivery of projects with impact evaluation is significantly timelier: common delays are avoided and the gap between planned and actual disbursements is reduced by half. Evidence-based mid-course corrections, a clearer implementation road map, strengthened capacity on the ground, and observer effects are possible channels to explain the results. Hopefully, this analysis will stimulate discussion over the optimal balance between project financing and the impact evaluation research needed to deliver development outcomes.